Protecting operations on qudits from noise by continuous dynamical decoupling - Napolitano, Reginaldo de Jesus; Fanchini, Felipe Fernandes [UNESP]; Silva, Adonai Hilario da; Bellomo, Bruno (Amer Physical Soc, 2021)
We develop a procedure of generalized continuous dynamical decoupling (GCDD) for an ensemble of d-level systems (qudits), allowing one to protect the action of an arbitrary multiqudit gate from general noise. We first present our GCDD procedure for the case of an arbitrary qudit and apply it to the case of a Hadamard gate acting on a qutrit. This is done using a model that, in principle, could be implemented using the three magnetic hyperfine states of the ground energy level of Rb-87 and laser beams whose intensities and phases are modulated according to our prescription. We show that this model allows one to generate continuously all the possible SU(3) group operations which are, in general, needed to apply the GCDD procedure. We finally show that our method can be extended to the case of an ensemble of qudits, identical or not.